2021
DOI: 10.1074/jbc.ra120.014616
|View full text |Cite
|
Sign up to set email alerts
|

ELK-1 ubiquitination status and transcriptional activity are modulated independently of F-Box protein FBXO25

Abstract: The mitogen-responsive, ETS-domain transcription factor ELK-1 stimulates the expression of immediate early genes at the onset of the cell cycle and participates in early developmental programming. ELK-1 is subject to multiple levels of posttranslational control, including phosphorylation, SUMOylation, and ubiquitination. Recently, removal of monoubiquitin from the ELK-1 ETS domain by the Ubiquitin Specific Protease USP17 was shown to augment ELK-1 transcriptional activity and promote cell proliferation. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…FBXO25 was reported to interact with ELK-1 and promote its polyubiquitination and degradation by the 26S proteasome, thereby impairing ELK-1 target gene transcription [ 88 ]. However, although subsequent, independent work confirmed that FBXO25 interacted with ELK-1 in a region including the CD, its proposed impact on ELK-1 ubiquitination or transcriptional activity could not be substantiated [ 89 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBXO25 was reported to interact with ELK-1 and promote its polyubiquitination and degradation by the 26S proteasome, thereby impairing ELK-1 target gene transcription [ 88 ]. However, although subsequent, independent work confirmed that FBXO25 interacted with ELK-1 in a region including the CD, its proposed impact on ELK-1 ubiquitination or transcriptional activity could not be substantiated [ 89 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
“…The USP17 family of DUBs comprises a number of very similar proteins originating from a cell-cycle regulated multicopy gene that has oncogene character in a range of cancer pathologies, albeit with noted exceptions [ 90 ]. USP17 was found to interact with ELK-1 in a region encompassing the B-domain and CD (aas 93–189) and efficiently deubiquitinate both mono- and polyubiquitinated ELK-1, thereby augmenting its transcriptional activity, driving target gene expression and cell cycle entry [ 86 , 89 ]. Moreover, expression of a hypo-ubiquitinated ELK-1 mutant, but not wild-type ELK-1, partially rescued the proliferation defect caused by USP17 depletion in HEK293T cells, illustrating the contribution of this mechanism towards mitogen signalling [ 86 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
“…Analysis of the transcription factor binding sites indicates that camel FGF21 promoter shared the most transcription factor binding sites with humans and mice ( Figure 3 ) although with significant differences in promoter sequences ( Figure 1 ) and binding site positions in the promoter. The major functional transcription factors such as SP1 [ 29 , 30 ], NF-1 [ 31 ], GATA1 [ 32 ], YY1 [ 33 ] and Elk-1 [ 34 ] nearly appeared in all mammals, suggesting that the signaling pathways involved in FGF21 gene transcription regulation are conservative in mammals. However, more work is still needed to identify differential transcription factors that can help reveal the specific regulatory patterns of camel FGF21.…”
Section: Discussionmentioning
confidence: 99%